Security log management identifying patterns in the chaos - Babbin, Jacob (Rockland, MA : Syngress, 2006)
This book teaches IT professionals how to analyze, manage, and automate their security log files to generate useful, repeatable information that can be use to make their networks more efficient and secure using primarily open source tools. The book begins by discussing the Top 10 security logs that every IT professional should be regularly analyzing. These 10 logs cover everything from the top workstations sending/receiving data through a firewall to the top targets of IDS alerts. The book then goes on to discuss the relevancy of all of this information. Next, the book describes how to script open source reporting tools like Tcpdstats to automatically correlate log files from the various network devices to the Top 10 list. By doing so, the IT professional is instantly made aware of any critical vulnerabilities or serious degradation of network performance. All of the scripts presented within the book will be available for download from the Syngress Solutions Web site. Almost every operating system, firewall, router, switch, intrusion detection system, mail server, Web server, and database produces some type of log file. This is true of both open source tools and commercial software and hardware from every IT manufacturer. Each of these logs is reviewed and analyzed by a system administrator or security professional responsible for that particular piece of hardware or software. As a result, almost everyone involved in the IT industry works with log files in some capacity. * Provides turn-key, inexpensive, open source solutions for system administrators to analyze and evaluate the overall performance and security of their network * Dozens of working scripts and tools presented throughout the book are available for download from Syngress Solutions Web site. * Will save system administrators countless hours by scripting and automating the most common to the most complex log analysis tasks.
Log analysis : overall issues -- IDS reporting -- Firewall reporting -- Systems and network device reporting -- Creating a reporting infrastructure -- Scalable enterprise Solutions (ESM deployments) -- Managing log files with Microsoft Log Parser -- Investigating intrusions with Microsoft Log Parser -- Managing Snort alerts with Microsoft Log Parser.
Includes index.
Keywords: Computer networks -- Security measures; Electronic books